Quantum Teaching Learning (QTL) Learning Model Innovation in PAI - Agung Cahya (LECTURES: Journal of Islamic and Education Studies, 2026)
Islamic Religious Education (PAI) in the modern era faces challenges such as declining learning motivation and the perception that religious instruction lacks relevance amidst the wave of digitalization. This study examines the innovation of the Quantum Teaching and Learning (QTL) model as a strategic solution to create an active, meaningful, and enjoyable PAI learning process. The study aims to analyze the fundamental concepts, principles, and application of QTL within the context of PAI, as well as to identify its innovations and impact on student learning outcomes. Employing a literature review and conceptual analysis approach, the study explores the QTL framework—grounded in the principle of "bringing their world into our world and taking our world into theirs"—and the TANDUR syntax (Grow, Experience, Name, Demonstrate, Repeat, Celebrate). The findings indicate that the key innovation of applying QTL to PAI lies in the integration of Islamic values—such as intention (*niyyah*), contemplation (*tafakkur*), trustworthiness (*amanah*), and gratitude (*syukr*)—into every stage of learning. This approach not only optimizes cognitive aspects but also holistically addresses the affective and psychomotor domains. The teacher's role shifts to that of a facilitator, motivator, and role model capable of fostering an inspiring learning environment. In conclusion, the QTL model proves relevant and effective in addressing contemporary PAI challenges and holds significant potential for shaping a generation of Muslims who are knowledgeable, faithful, and possess noble character.